A research of semantic field Semantic Field of Oral Activity in Sasak Language in The Ampenan District - Sulistiawangi; Burhanuddin; Ratna Yulida Ashriany (Program Studi Magister Ilmu Linguistik Universitas Warmadewa, 2024)
This research is entitled Semantic Field of Oral Activity in Sasak Language at Ampenan District. The aim of this research is to classify and analyze the components of the oral activities in Ampenan District. This is qualitative research that uses a descriptive approach. To collect data, this research uses the introspection method; listening method with tapping techniques, uninvolved listening techniques, note-taking techniques; and cakap (speak) method. Furthermore, to analyze the data, this research used the intralingual matching method to classify lexemes of the semantic field and the extra-lingual matching method to analyze the components of each lexeme. Meanwhile, to present the results of the analysis, both formal and informal methods are used. The data of this research include lexemes of the semantic field of oral activity and the components of each lexeme in the Sasak language. A total of 30 oral activity lexemes were found to occupy the semantic field with the classification: (1) the oral activity, to eat, (2) to drink, (3) to speak, (4) to make sounds, and (5) to produce something (besides sound) from the mouth.